Performance Test and Operational Cost Analysis of the Jajar Legowo RTP-2040 Rice Transplanter in Padaelo Village, Lamuru District - Muhammad Yusuf, Tahir; Iqbal; Mursalim (Salaga Journal, 2024)
Rice fields are used as an alternative to achieve food self-sufficiency because they have many advantages such as providing lots of water, land close to rivers, and the ability to choose land for farming. So this research is needed to determine the work efficiency and operational costs of the Jajar Legowo RTP 2040 rice transplanter. So that it can maximize the performance of this planting tool when it is later used by farmers. The aim of this research is to determine the work efficiency and operational costs of the Jajar Legowo RTP 2040 rice transplanter on rice fields in Bone Regency. The procedure used begins with the seeding stage, land processing, and the rice transplanter operation stage. The Jajar Legowo RTP 2040 rice transpanter was operated with a test distance of 10 x 10 m and carried out 3 repetitions using a speed of 2 km/hour on the land according to the planting work pattern. The results of this research obtained a KLT value of 0.257 ha/hour, KLE of 0.193 ha/hour, and field efficiency of 75.15%. Meanwhile, the wheel slip value obtained was 15.42. As for the cost analysis, the fixed costs are obtained at Rp.8.842.988,-/year, while the total variable costs are Rp. 5.154.240,-/year. Basic operational costs obtained are IDR. 13.997.228.-/year.